A Conceptual Summary of the Application of Free Modules in the Applied Mathematical Science - Khairiah Rahmah Virda Sari; Sisilia Sylviani (PT Anugrah Teknologi Kecerdasan Buatan, 2026)
Modules are one of the topics studied in algebra, furthermore there are free modules which are a subtopic of the module itself. This literature aims to find out the application of free modules in various branches of mathematics, both explicitly described and implicitly discussed in previous literatures. So that, this research used the Systematic Literature review to find the applications of module theory, especially the application of free modules in previous research. There are applications of free modules in various fields that are quite often discussed in system control theory, representation theory, cryptography, and mathematical physics. This research reveals that free modules not only play a role in pure algebra theory, but also have practical applications in various other sectors of science. This research is useful for future research to find out the application of modules, especially free modules, to research them in more depth.